Experience with denosumab therapy for osteoporosis in rheumatoid arthritis patients receiving glucocorticoids - I. S. Dydykina; P. S. Kovalenko; A. V. Smirnov; S. I. Glukhova; E. L. Nasonov (Современная ревматология)
Rheumatoid arthritis (RA) therapy is aimed not only at suppressing inflammation, but also at preventing local and generalized bone loss, particularly in patients receiving glucocorticoids (GCs). Denosumab, a fully human monoclonal antibody that binds to the receptor activator of nuclear factor kappa B ligand (RANKL), prevents interaction with the receptor on osteoclasts, reduces their activity, and inhibits bone resorption is a promising drug for the treatment of secondary osteoporosis (OP).Objective: to assess bone mineral density (BMD) in the axial and peripheral skeleton, erosive and destructive changes in the hands and feet of GC-treated patients with RA 12 months after denosumab treatment.Patients and methods. Sixty-six postmenopausal women suffering from RA with a documented diagnosis of OP received denosumab 60 mg subcutaneously twice: at baseline and 6 months later. BMD was measured before treatment and after 12 months of follow-up, by using dual-energy X-ray absorptiometry of three sections: the lumbar spine (LI–IV), femoral neck (FN) and distal forearm (DF). A change in Sharp/van der Heijde (SvH) scores, as well as the number of erosions and narrowed articular slits, and total scores were assessed, by using hand and foot radiographs, at baseline and after 12 months.Results and discussion. The mean age of the patients was 59.6±7.4 years; the mean duration of RA was 17.7±10.4 years. All the patients received anti-inflammatory therapy, including 34 (49.3%) patients who took GCs. In this group, pre- and posttreatment BMD in LI–IV was 0.809±0.109 and 0.849±0.117 g/cm2 , respectively (p < 0.0001); that in FN was 0.598±0.087 and 0.609±0.083 g/cm2 (p=0.045); and that in DF was 0.496±0.113 and 0.498±0.106 g/cm2, respectively (p>0.05). Regardless of the nature of anti-inflammatory therapy (with/without GCs), BMD in LI–IV and FN increased significantly DF stabilized in both patient groups. Before/after denosumab treatment, the GC (GC+) group showed a significant increase in the number of erosions up to 32.5 [13.0; 78.0] and 33.0 [13.0; 90.0] scores, respectively (p=0.043) and in the total SvH scores up to 146.5 [93.0; 221.0] and 149.0 [930; 221.0] respectively (p=0.027). There was no increase in the number of narrowed slits in the GC+ group. The number of erosions, narrowed articular slits, or the total SvH scores did not significantly change in the group of patients who did not receive GC (GC-).Conclusion. Therapy with subcutaneous denosumab 60 mg 2 times yearly at semiannual intervals could significantly increase BMD in LI–IV and FN and stabilize in DF regardless of GC use. Negative changes in the number of erosions and total SvH scores were noted mainly in the GC+ group. The SvH scores for the hands and feet remained unchanged in the patients of the GC- group.